2017
DOI: 10.3851/imp3169
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Disoproxil Fumarate Monotherapy is Superior to Entecavir-Adefovir Combination Therapy in Patients with Suboptimal Response to Lamivudine-Adefovir Therapy for Nucleoside-Resistant HBV: A 96-Week Prospective Multicentre Trial

Abstract: TDF therapy achieved a better complete virological response than ETV-ADV therapy in chronic hepatitis B patients with suboptimal response to long-term LAM-ADV rescue therapy. (KCT0000627).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Some previous studies demonstrated that previous ADV-experienced patients have inferior efficacy of TDF compared with NA-naïve patients 28. Some reported TDF mono-therapy showed superior efficacy compared with LMV plus ADV or ETV plus ADV in LAM-R CHB patients 29,30. As a combination strategy, regarding previous reports, the efficacy of TDF mono- and combination treatments was similar,31 and TDF-ETV combination therapy revealed a high rate of achieving virologic suppression regardless of prior treatment experience without resistance 32…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies demonstrated that previous ADV-experienced patients have inferior efficacy of TDF compared with NA-naïve patients 28. Some reported TDF mono-therapy showed superior efficacy compared with LMV plus ADV or ETV plus ADV in LAM-R CHB patients 29,30. As a combination strategy, regarding previous reports, the efficacy of TDF mono- and combination treatments was similar,31 and TDF-ETV combination therapy revealed a high rate of achieving virologic suppression regardless of prior treatment experience without resistance 32…”
Section: Discussionmentioning
confidence: 99%
“…[1 [1][2][3][4][5][6][7][8][9][10][11][12] Currently, the US Food and Drug Administration (FDA) has approved two types of anti-hepatitis B virus drugs: interferon (IFN) and nucleos(t)ide analogs (entecavir, lamivudine, telbivudine, adefovir, and tenofovir), although nucleoside analogues are well tolerated and exhibit an early and potent antiviral effect, the selection of resistant mutants and nephrotoxicity during long-term therapy limit their use. [ [13][14] Chinese herbal medicine (CHM), as one of the most popular complementary and alternative therapies of CHB, a large number of studies have reported its anti-hepatitis B virus effect. CHMs have two major characteristics: a) it is flexible and variable in various kinds of herbal medicines, it has complex compositions which means not easy causing drug resistance.…”
Section: Abstract Chronic Hepatitis B Cirrhosis Traditional Chinesementioning
confidence: 99%
“…It was reported that long-term treatment with ETV, Lamivudine(LDV), or Tenofovir(TDF) could reverse HBV-related cirrhosis to milder brosis [4] . However, the selection of resistant mutants and nephrotoxicity during long-term therapy limit its use [5][6] . Therefore, the treatment goals for LC patient are to maximize long-term inhibition of HBV replication [7] , reducing liver cell in ammation and necrosis and liver brous tissue hyperplasia, delaying and reducing the occurrence of liver failure, decompensation of LC, HCC and other complications, improving the quality of life of patients, and extending their survival time, and for some patients could pursued the clinical cure [8][9] .…”
Section: Introductionmentioning
confidence: 99%